Evaluation and Identification of Promising Introgression Lines Derived From Wild Cajanus Species for Broadening the Genetic Base of Cultivated Pigeonpea [Cajanus cajan (L.) Millsp.] - Sharma, Shivali; Paul, Pronob J.; Kumar, C.V. Sameer; Rao, P. Jaganmohan; Prashanti, L.; Muniswamy, S.; Sharma, Mamta (Frontiers in Plant Science, 2019)
Pigeonpea (Cajanus cajan (L.) Millsp.), a multi-purpose and nutritious grain legume crop, is cultivated for its protein-rich seeds mainly in Asia and Eastern and Southern Africa. In spite of large breeding efforts for pigeonpea improvement in India and elsewhere, genetic enhancement in this crop is not adequate, which is mainly due to its narrow genetic base and various biotic and abiotic stresses. Equipped with many useful genes including biotic and abiotic stress resistance, wild Cajanus species provide novel genetic variations for the genetic upgradation of pigeonpea cultivars. In the present study, 75 introgression lines (ILs) derived from wild C. cajanifolius and C. acutifolius were evaluated for yield and related traits in varied environments across locations (MET 01 and MET 02) and years (Trial 03 and Trial 04). Restricted Maximum Likelihood (REML) analysis revealed large genetic variation in all the four trials for all the traits evaluated. Superior ILs with medium maturity duration identified in this study is believed to replace the widely cultivated variety ICPL 87119 in the near future. Besides this, promising high-yielding ILs in mid-early duration group have the potential to develop new cultivars which fit well in short cropping duration. Additive main effects and multiplicative interaction (AMMI) analysis for the multi-location trials identified ICPL 15023 in MET 01 and ICPL 15072 in MET 02 as most stable ILs in all locations- Gulbarga, Warangal, Tirupati, and Patancheru. Pods Plant-1 and pod weight Plant-1 emerged as most contributing traits from both correlation and principal component analysis of Trials-03 & 04. Nine ILs in Trial 03 and 11 in Trial 04 showed complete resistance (0%) for the sterility mosaic diseases (SMD) and Fusarium wilt (FW). The noble genetic variability found in the superior ILs over the popular check with high levels of resistance for important diseases ~SMD and FW can be further released as varieties for different agro-ecological regions. Inclusion of few ILs in the variety release programs of India has initiated the process already. These lines can also be used as new diverse sources of variations in pigeonpea breeding programs to develop new cultivars with a broad genetic base.